RADIOLOGIC DIAGNOSIS OF CHRONIC LUNG COMPLICATIONS IN THE POSTCOVID-19 PNEUMONIA PERIOD - O.R. Teshaev,; G.E. Rakhmonova,; D.Z. O‘ktamova,; D.Z. O‘ktamov, (Central Asian Journal of Medicine, 2025)
In early 2020, we reached the first SARS-CoV-2 peak of transmission and contamination, which led to a large number of fatalities worldwide [1]. Initially, efforts were focused on controlling the infectious process in order to prevent lung attack and respiratory insufficiency [2,3]. In infected individuals, altered levels of oxygenation in arterial blood and the depletion of gas exchange caused severe deficiencies and losses of pulmonary capacitance, compromising the basic functions of life [4]. Post-acute complications include secondary infections, impaired lung function, pulmonary artery thromboembolism, pulmonary hypertension, and pulmonary fibrosis. The main risk of non-timely and ineffective treatment of pneumonia is respiratory insufficiency, purulent pleurisy, scar transformation of lung tissue (fibrosis), sepsis, lung abscess, multiorgan insufficiency.